Rebuilding Education under Global Challenges: Integrating Sustainability into Economics and Management Curricula - Huttmanová, Emília; Mikča, Radoslav (European Journal of Sustainable Development, 2025)
Current global challenges and the dynamics of ongoing changes significantly influence modern university education. Despite the diversity of study programs across universities, it is essential to consider the appropriate integration of contemporary social and environmental topics into educational curricula. The Faculty of Management and Business (FMB) at the University of Prešov focuses on education in the fields of economics and management. Therefore, the education of future economists, entrepreneurs, and managers should also incorporate elements of sustainability, circular economy, and proenvironmental approaches in both production and consumption activities. The aim of this paper is to evaluate the perceptions and attitudes of students (future entrepreneurs, economists and managers), towards the integration of "green topics" into educational content and their application in practice. The results of the questionnaire survey were complemented by the perspectives of teachers through structured interviews, aimed at identifying the need for and possible ways of incorporating green topics into the curriculum from their point of view. The collected data were analysed using a mixed methods approach, combining both qualitative and quantitative research methods, including inductive inference methods. The results served as input for the development of new study programs. Based on these findings, we also formulate proposals aimed at "greening" the existing curricula through the use of creative and participatory forms of education. Key words: global challenges, education, green topics, sustainability